Social Inclusion, Entrepreneurial Intention, Self-Efficacy, Gender, And Entrepreneurship Education In Generation Z - Almaitsya Gianis; Abdul Haeba Ramli; Siti Mariam (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Generation Z is a group that has enormous potential in the world of entrepreneurship in the technological era. Therefore, further research on factors that influence entrepreneurial intention among Generation Z is needed. This study aims to analyze whether social inclusion, entrepreneurial intention, self-efficacy, and entrepreneurship education have a significant impact on Generation Z's entrepreneurial intention, and whether this influence is moderated by gender. This study uses a quantitative approach using a survey. Data were collected through questionnaires given to 190 members of Generation Z who were born between 1998 and 2009 and domiciled in Tangerang. The data analysis method uses the Structural Equation Model (SEM). The results of the study indicate that self-efficacy, social inclusion, and entrepreneurship education have a significant effect on entrepreneurial intention, social inclusion has a significant effect on self-efficacy, self-efficacy has a significant effect on mediating the relationship between social inclusion and entrepreneurial intention. In addition, gender significantly moderates the relationship between social inclusion and entrepreneurial intention. The implications of this study emphasize the importance of increasing self-efficacy and access to entrepreneurship education for Generation Z to encourage entrepreneurial intention. In addition, a gender-based approach in entrepreneurship policies and programs can increase the effectiveness of interventions that support young people in entering the business world. Keywords: Social Inclusion, Entrepreneurial Intention, Self-Efficacy, Gender, Entrepreneurship Education.